Socialization, Historical Narrative, Comparison - Dénes, Iván Zoltán (Per Aspera ad Astra, 2025)
On 17-18 April 2024, the Henrik Marczali Research Group held a two-day conference to commemorate the life and work of Henrik Marczali, who played a significant role in the establishment of professional historiography and the training of historians in Hungary. This issue presents the papers presented and discussed at the conference in the thematic units of socialisation, historical narrative and comparison.